Histochemical changes of NADPH-diaphorase in Guillain–Barre syndrome - A. V. Sakharova; S. M. Lozhnikova; M. A. Piradov; V. N. Pirogov (Анналы клинической и экспериментальной неврологии, 2017)
The distribution of NADPH-diaphorase activity in peripheralnerve biopsy was studied to evaluate the role of nitric oxide indemyelination.NO is an important inflammatory mediator which appears toexert significant effects in number of demyelinating diseases, andsometimes is established a direct causal link between NO anddemyelination. Till now there wasnt any description for theinvolvement of nitric oxide in GBS cellular immune reactions.We have studied cellular and subcellular histochemistry ofNADPHdiaphorase in GBS. Peripheral nerve biopsy tissueswere examined with regard to disease duration, from 6 patientswho were 11 to 52 days after onset of symptoms.Tetrazolium method in our modification was used to visualizeNADPHdiaphorase reaction in the successive tissue sections onthe cellular and ultrastructural levels. We have shown that specificpattern of histochemical reaction was characteristic foreach distinct time point of disease duration. Up and downregulationmode of histochemical reaction was different forSchwann cells (SC) and mononuclear inflammatory cells.During demyelination reduced NADPH-diaphorase activity wasfound in SCs associated with degrading myeline sheath. Duringremyelination that characterized by proliferation of SCs andenlarge of its cell volume we observed an increase inNADPH-diaphorase reaction that indicated on the rise of theNO production in it. In that activated SCs the intracellular distributionof NADPH-diaphorase is changed. Maximum of reactionintensity was shifted in nucleus. It suggests the appearanceof the expressional regulation in SCs, which characteristic forthe highoutput iNOS, and directed to increase of NO productionThe levels of NADPH-diaphorase activity varied in large extendin different recruited macrophages in the same tissue sample. Itreflects the cyclic character proper to macrophagal iNOS.Intensive reaction was found in cytoplasm and nuclear envelopof the mononuclear cells, that migrate throw the blood vesselwalls where NO may enhancing local nerve blood flow and servesimultaneously as important effector in the clearance of themyelin/axonal debris.High intensive NADPH-diaphorase activity was detected in distinctcytoplasm regions of the macrophage on the territory of theinjured myelin sheath. Hyperproduction of nitric oxide andcytotoxic effect may take place in such districts.All this findings suggest that endogenous nitric oxide is involvedin pathogenesis of GBS.